POOR SURVIVAL OF ABG I HIP PROSTHESIS IN YOUNGER PATIENTS - Gallo, Jiri; Langova, Katerina; Havranek, Vitezslav; Cechova, Ivana (Biomedical papers, 2008)
Background: Hydroxyapatite coated (HAC) hip implants have been used in clinical practice for more than two decades. However, the majority of studies have reported only intermediate term outcomes that are not reliable for predicting long-term behavior in all implants. The aim of this study was to determine the performance of HAC total hip arthroplasty in younger patients over a 10-year follow-up period.Methods and Results: This was an observational retrospective study of a 137 consecutive hips with the ABG I prosthesis. Of these, 128 were available for the last investigation. Median duration of follow-up was 10.9 years. The mean age at time of index surgery was 46±6.7 years. Probability of implant survival was estimated using the Kaplan-Meier method. The overall 12-year cumulative survival was 0.55 (95% CI, 0.443-0.659). Periprosthetic osteolysis (57 %) was the most frequent reason for failure followed by aseptic loosening (28 %). When only aseptic loosening was included in the analysis, the same figures for cup and stem were 0.873 (95% CI, 0.808-0.938) and 0.992 (95% CI, 0.976- 1.0), respectively. Patients with a smaller cup size were those at high risk for revision due to wear-related complications (odds ratio, OR=4.3; 95% CI, 1.734-10.555).Conclusion: This study reports one of the poorest 12-year survivorship data for cementless acetabular component in the literature. The main reason for premature failure was osteolysis, strongly related to high wear rate of polyethylene.
Keywords: Keywords: Total hip arthroplasty/ABG I/Survival analysis/Hydroxyapatite coating/ Osteolysis